2020
DOI: 10.7759/cureus.8606
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Closed Incision Negative Pressure Therapy Immediately After Total Ankle Arthroplasty Surgeries

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A previous report showed that patients needed a skin flap procedure in 1.9% of primary TAAs because of wound problems, and then, among them, 21.1% of patients had flap failures [ 6 ]. While it is reported that a significantly decreased incidence of wound healing problems after primary total ankle arthroplasty was seen using incisional NPWT dressings [ 7 , 8 ]. So, NPWT would be also useful to be utilized for infectious wound dehiscence after TAA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that patients needed a skin flap procedure in 1.9% of primary TAAs because of wound problems, and then, among them, 21.1% of patients had flap failures [ 6 ]. While it is reported that a significantly decreased incidence of wound healing problems after primary total ankle arthroplasty was seen using incisional NPWT dressings [ 7 , 8 ]. So, NPWT would be also useful to be utilized for infectious wound dehiscence after TAA.…”
Section: Discussionmentioning
confidence: 99%